2019
DOI: 10.1038/s41467-019-09354-z
|View full text |Cite
|
Sign up to set email alerts
|

Semi-solid prodrug nanoparticles for long-acting delivery of water-soluble antiretroviral drugs within combination HIV therapies

Abstract: The increasing global prevalence of human immunodeficiency virus (HIV) is estimated at 36.7 million people currently infected. Lifelong antiretroviral (ARV) drug combination dosing allows management as a chronic condition by suppressing circulating viral load to allow for a near-normal life; however, the daily burden of oral administration may lead to non-adherence and drug resistance development. Long-acting (LA) depot injections of nanomilled poorly water-soluble ARVs have shown highly promising clinical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 25 publications
1
36
1
Order By: Relevance
“…Our group has used similar strategies to develop hydrophobic prodrug nanoformulations of the HIV integrase inhibitors CAB and dolutegravir that extended their antiretroviral efficacy for more than a month 11,25. Others reported improvements in antiretroviral activity and cellular uptake with other FTC prodrugs 35,45. However, in contrast to our current study, some prodrugs were less hydrophobic and not encased in nanoformulations 46.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Our group has used similar strategies to develop hydrophobic prodrug nanoformulations of the HIV integrase inhibitors CAB and dolutegravir that extended their antiretroviral efficacy for more than a month 11,25. Others reported improvements in antiretroviral activity and cellular uptake with other FTC prodrugs 35,45. However, in contrast to our current study, some prodrugs were less hydrophobic and not encased in nanoformulations 46.…”
Section: Discussioncontrasting
confidence: 59%
“…While prior studies had attempted to generate a longer acting FTC prodrug, none were fully characterized or developed as a LA ARV strategy 35. In addition, critical measurement of FTC TP formation was lacking as well as in vivo and drug tissue biodistribution assays 35.…”
Section: Discussionmentioning
confidence: 99%
“…The main focus of HIV research is to develop strategies that prolong protection and target latent HIV + cells. Recent studies have demonstrated designing a long-acting (LA) ARV delivery system would boost the HIV treatment strategy [10][11][12][13]. The nanoformulated ARV delivery system has been shown to enhance drug-solubility, stability, biodistribution, pharmacokinetics, e ciency, and concurrent drug safety, due to reduced ARV associated side-effects [14][15][16].…”
mentioning
confidence: 99%
“…Licensed LAIs are available for contraception [21], schizophrenia [22,23], opioid addiction [24], androgen ablation [25], and hypogonadism [26]. LAI medicines are also in late stage development for the treatment of HIV [27], with preclinical proof-of-concept emerging across infectious diseases [28,29,30].…”
mentioning
confidence: 99%